Medical Students’ Attitude towards Endotracheal Intubation in - Khajavikhan, Javaher; Seidinia, Mohammad Reza; Zarosh kord, Mojtaba; Peyman, Hadi; Sayehmiri, Kourosh; Ashrafi Hafez, Asghar (Advances in Nursing & Midwifery, 2013)
Abstract Introduction: Airway management capabilities, is critical skills for safe anesthesia .Difficult or failed airway management, is a major cause of accidents and deaths related to anesthesia. Given that survival depends on maintaining his airway management, is necessary for a physician who is fully aware of all its aspects. The aim of this study is to investigate of factors related to endotracheal intubation was performed correctly. Materials and Methods: In a descriptive study 104 medical students were selected by convenience sampling. Data were collected by questionnaires. Data analyzed using Mann-Whitney, Kruskal- Wallis, ANOVA and Pearson correlation coefficient tests. Findings: Of 104 samples39.4 % were males.َMean age was 23.62 ± 1.19.Skills of intubation in 53.8% of samples were moderate, in 5.8 % were excellent. Overall 65.4 % of individuals after learning intubation in the operating room, said that the previous drill -down on average model was effective. Main reasons for the failure of endotracheal intubation were fear of harm to patients intubated (mean score 4.29 of 5), distrust of teachers and anesthesiologist toward the students (4.23) and stress and anxiety in the operating room (4.21), and Low theoretical information (3.94). There was not any Significant association between students’ scores in evaluating teacher in education of intubation, assessment score of training the model and academic years of student .There was a significant relationship between academic years student and fear of harm to the patient during intubation (p<0.02). Conclusion: Fear of harm to patients intubated, distrust of teachers and anesthesiologist toward the students and stress and anxiety in the operating room were most important factors affect the success of endotracheal intubation in the operating room. Keywords: Endotracheal intubation, Medical students, Perspective